Biological denitrification with a novel biodegradable polymer as carbon source and biofilm carrier - Wu, Weizhong; Yang, Feifei; Yang, Luhua (BIORESOURCE TECHNOLOGY, 2012)
A novel biodegradable polymer composed of PHBV and PLA was prepared for advanced wastewater treatment. It could serve as both biofilm carrier and carbon source for denitrification. Results of batch test showed the average denitrification rate was 0.07 mg NO3-N/(g h). The kinetic study demonstrated that when nitrate concentration was above 10.00 mg/L, DOC could not be detected in the effluent. In continuous packed-bed reactor, the average nitrogen removal efficiency was 94.11%. Nitrite concentration throughout the experiment was below 0.15 mg/L. The formation of NH4-N was observed, though small. DOC released in the effluent did not exceed 16.00 mg/L in the whole process, and it finally dropped below 1.20 mg/L. (C) 2012 Elsevier Ltd. All rights reserved.